2017
DOI: 10.1016/j.saa.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative observation of reversible phase change in astrochemical ethanethiol ices using infrared spectroscopy

Abstract: Here we report the first evidence for a reversible phase change in an ethanethiol ice prepared under astrochemical conditions. InfraRed (IR) spectroscopy was used to monitor the morphology of the ice using the SH stretching vibration, a characteristic vibration of thiol molecules. The deposited sample was able to switch between amorphous and crystalline phases repeatedly under temperature cycles between 10K and 130K with subsequent loss of molecules in every phase change. Such an effect is dependent upon the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
(15 reference statements)
2
7
0
Order By: Relevance
“…We have already cited numerous papers that relate to the present study, but they are mainly from the older literature. Two recent publications that are close to our work are those of Pavithraa et al (2017aPavithraa et al ( , 2017b on ethanethiol and 1-propanethiol respectively. Since those papers did not include ice thicknesses or band intensities, it is impossible to make quantitative comparisons to our results.…”
Section: Comparisons To Recent Worksupporting
confidence: 84%
“…We have already cited numerous papers that relate to the present study, but they are mainly from the older literature. Two recent publications that are close to our work are those of Pavithraa et al (2017aPavithraa et al ( , 2017b on ethanethiol and 1-propanethiol respectively. Since those papers did not include ice thicknesses or band intensities, it is impossible to make quantitative comparisons to our results.…”
Section: Comparisons To Recent Worksupporting
confidence: 84%
“…They also describe changes in spectra, sometimes quite subtle, observed as the concentration of ethanethiol isolated in an Ar ice is increased from 1:500 up to bulk ethanethiol ice. Our own spectra most resemble the highest dilution of ethanethiol observed by Barnes et al but have a lower contribution from dimers and other multimers of ethanethiol and, in spite of their qualitative similarity, should not be confused with spectra of bulk ethanethiol ice presented by Barnes et al or Pavithraa et al (Figures S3–S6). The vibrational band positions reported for Ar isolated ethanethiol from Barnes et al are presented along with our own measurements in Table .…”
Section: Resultssupporting
confidence: 75%
“…In the case of ethanethiol, Pavithraa et al (2017a) showed that warming of a low-temperature ice resulted in a phase change from amorphous to crystalline at 110 K. Interestingly, further warming of the ice caused the phase to switch back to amorphous at 125 K. These phase changes were found to be reversible, also occurring during cooling of the ice.…”
Section: Spectroscopy Of Candidate Sulfur-bearing Moleculesmentioning
confidence: 98%
“…However, for successful detections of interstellar molecules to be made spectroscopically, it is necessary to have their corresponding laboratory-generated spectra at relevant temperatures. For example, recent studies have explored in great detail the IR and ultraviolet (UV) spectra of thiol compounds, including methanethiol, ethanethiol, 1-propanethiol, and 2-propanethiol (Hudson 2016(Hudson , 2017Pavithraa et al 2017aPavithraa et al , 2017bHudson and Gerakines 2018). Although detections of the two smaller molecules in interstellar environments have been confirmed (Linke et al 1979;Kolesniková et al 2014), the latter two remain candidate molecules (Gorai et al 2017).…”
Section: Spectroscopy Of Candidate Sulfur-bearing Moleculesmentioning
confidence: 99%